Perkiraan Keadaan Perekonomian Kota Pekalongan Melalui Indikator Dini - Chalimah . (Jurnal Ekonomi Dan Bisnis, 2015)
Ekonomi Development in Pekalongan city had to attention in district economi issues. The meaning of economic development was effort had to done by government and planned in certainty time for changing and rising public walfare level. One of economix development aspects was economix grownth with only see 3 indicator factors were PDRB, Income percapita dan population growth.This research purposes were to know economic and bussinses indicator include index of coincident indicators, index of leading indicator, bussiness confidence index and consumer confidence index.The result research of the study indicate that PDRB and composit coincident index move to gether, but since 1998 : 4 condition changed where this both indexes move to far and not stabilily move, example 1991: I , 2 ; 2000 : 3 . 4 : 2001 : 1 , 3 both indexes had different arrow and 1999 :3.4:2000: 1 ,2 ; 2O01: 2 .4 both indexes had same arrow. This condition was becaused instability economy in economic crisis and political change in Indonesia. Index of leading indicator in first threemonths period tend lead PDRB index wilh moving arrow until 1991 : 1 , except 1996: 1 ,3 , 4 : 1997 : 2 ; 1998 : 3 , 4 Since 1992 : 2 both indexes too far, however they can be growth economy.Coincident index can be also predicted PDRB index. First threemonths 2002 decreased about - 0,01 for fourth threemonths 2001.. Index of leading indicator can be predicted third threemonths 2002 will be increased together with increase economic index about 0,207.